Determinants Of Malaysia’s Resource-Based Rubber Medical Devices Export - Lee, Siu Ming (2019)
Malaysia is a world leading resource-based rubber medical devices (RMD) exporter and has remarkable success in the value-added RMD export rather than depending on exporting the raw rubber. However, Malaysia faces the challenges of decreasing market share due to increasing competition from other countries, and stagnating RMD market share. This study examines the determinants of Malaysia’s RMD export for 1989-2013. Empirical techniques used are Pooled Ordinary Least Squares (OLS), panel estimation of fixed (FE) and random effect (RE) and Poisson pseudomaximum likelihood. Findings show that the key determinants in terms of exporter’s and importers’ income and manufacturing industry incomes (separate estimations) are significant in the gravity model. Distance (a proxy for transportation cost) was insignificant but Logistic Performance Index provides the explanation that a country with less developed logistics infrastructure may make transporting costlier to a nearby country. Importers with higher healthcare expenditure per capita showed significance in increasing Malaysia’s RMD import while countries with number of people living with HIV/AIDS (indicating disease awareness, infection prevention and control) are not significant in reducing import of Malaysia’s RMD. All Malaysia’s bilateral FTA partners show significant negative relationship in terms of lower imports relative to other non-bilateral FTA partners especially compared against the export to high income, large countries, relatively.